BOOK REVIEW: ONLINE TEACHING OF ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA: LESSONS FROM COVID-19 PANDEMIC - Tanjung, Firima Zona (LLT Journal: A Journal on Language and Language Teaching, 2022)
The last two years have forced educators and learners to be digitally-literate or at least adaptable to the digital technology use drastically because of COVID-19 pandemic. This globally challenging condition was then captured and written by Didi Suherdi (2021) and published by Deepublish. Online Teaching of English as a Foreign Language in Indonesia: Lessons from Covid-19 Pandemic consists of seven chapters. It aims to provide new theoretical and practical insights of English teaching through online mode in the midst COVID-19 pandemic, specifically in Indonesia. This book covers various topics related to the research studies and notions of utilizing ICT as well as optimizing educators’ roles in the context of online teaching-learning process. Additional topics are also presented to promote the use of alternative ICT-based teaching models and teacher training in the online setting. Distinctively, this book is recommended for academicians who are concerned about ICT-use and eager to start an initial step to integrate and take advantage of ICT for the resiliency of the education system in the post-pandemic era.